2015
DOI: 10.3109/00498254.2015.1060372
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and metabolism of cabotegravir: a comparison of biotransformation and excretion between different species and routes of administration in humans

Abstract: 1.  Cabotegravir [(3S,11aR)-N-[(2,4-difluorophenyl)methyl]-6-hydroxy-3-methyl-5,7-dioxo-2,3,5,7,11,11a-hexahydro[1,3]oxazolo[3,2-a]pyrido[1,2-d]pyrazine-8-carboxamide] is an HIV-1 integrase inhibitor under development as a tablet for both oral lead-in therapy and long-acting (LA) injectable for intramuscular dosing. 2. Metabolism, pharmacokinetics and excretion were investigated in healthy human subjects who received either a single oral dose (28.2 mg) of [(14)C]cabotegravir in a mass balance study, or LA form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 20 publications
5
56
0
Order By: Relevance
“…Cabotegravir is primarily metabolized by uridine diphosphate glucuronosyltransferase (UGT) 1A1 with a minor contribution by UGT 1A9 6. At clinically relevant concentrations, CAB does not inhibit or induce the major cytochrome P450 (CYP) or UGT enzymes in vitro and had no significant effect on the pharmacokinetics (PK) of midazolam, a sensitive CYP3A4 probe substrate 7.…”
Section: Introductionmentioning
confidence: 99%
“…Cabotegravir is primarily metabolized by uridine diphosphate glucuronosyltransferase (UGT) 1A1 with a minor contribution by UGT 1A9 6. At clinically relevant concentrations, CAB does not inhibit or induce the major cytochrome P450 (CYP) or UGT enzymes in vitro and had no significant effect on the pharmacokinetics (PK) of midazolam, a sensitive CYP3A4 probe substrate 7.…”
Section: Introductionmentioning
confidence: 99%
“…It is a class 2 compound (Biopharmaceutics Drug Disposition Classification System) exhibiting high passive permeability and low solubility . Cabotegravir is primarily metabolized by uridine diphosphate glucuronosyltransferase (UGT)1A1 with a minor contribution by UGT1A9 to form glucuronic acid conjugates . The primary metabolite, M1, and unchanged cabotegravir are both excreted in bile.…”
mentioning
confidence: 99%
“…8 Cabotegravir is primarily metabolized by uridine diphosphate glucuronosyltransferase (UGT)1A1 with a minor contribution by UGT1A9 to form glucuronic acid conjugates. 9 The primary metabolite, M1, and unchanged cabotegravir are both excreted in bile. Due high intrinsic membrane permeability, the impact of efflux transporters on intestinal absorption of cabotegravir is minimal.…”
mentioning
confidence: 99%
“…Cabotegravir is metabolized via UDP-glucuronosyltransferase (UGT) 1A1, with a secondary contribution from UGT1A9 to inactive glucuronide metabolites. 6 The primary metabolite of cabotegravir (M1) is an ether glucuronide excreted predominantly in urine. In vitro, cabotegravir has not been shown to inhibit or induce UGT and cytochrome P450 (CYP) enzymes.…”
mentioning
confidence: 99%
“…8 Overall, cabotegravir has a favorable drug interaction profile and is expected to have few clinically significant drug interactions. 6 In accordance with the International Conference on Harmonization (ICH) recommendations for new agents, 9 supratherapeutic doses of INSTIs have been examined for their potential to affect cardiac repolarization and have not been shown to have significant effects on the QTc interval. 10,11 In nonclinical studies, no effects of cabotegravir on cardiac conduction have been observed.…”
mentioning
confidence: 99%